Metformin differentially activates ER stress signaling pathways without inducing apoptosis - Thomas Quentin; Michael Steinmetz; Andrea Poppe; Sven Thoms (The Company of Biologists, 2012)
SUMMARY Endoplasmic reticulum stress signaling (ERSS) plays an important role in the pathogenesis of diabetes and heart disease. The latter is a common comorbidity of diabetes and worsens patient outcome. Results from clinical studies suggest beneficial effects of metformin - a widely used oral drug for the treatment of type 2 diabetes - on the heart of diabetic patients with heart failure. We therefore analyzed the effect of metformin on ERSS in primary rat cardiomyocytes. We found that metformin activates the PERK-ATF4 but not the ATF6 or IRE1-XBP1 branch in ERSS and leads to a strong upregulation of CHOP mRNA and protein. Surprisingly, long-term induction of CHOP by metformin is not accompanied by apoptosis even though CHOP is regarded to be a mediator of ER-stress-induced apoptosis. In conclusion, metformin induces distinct ER stress pathways in cardiomyocytes and our results indicate that CHOP is not necessarily a mediator of apoptosis. Metformin might exert its cardioprotective effect through selective activation of ERSS pathways in the cardiomyocyte.